Retraction: "Climate Change and Internal Migration in India: Response of the State, Market, and the Civil Society, " by Anil Kumar Jha. Issue 1 (4th February 2016) - Unknown
Abstract : The above article from Poverty & Public Policy, published online: 14 JUN 2013 in Wiley Online Library (wileyonlinelibrary.com ) and in Volume 5, No. 2, pp. 133–145, has been retracted by agreement between the journal Editor in Chief, Max J. Skidmore, and Wiley Periodicals, Inc. The retraction has been agreed to because of plagiarism; there is considerable unattributed overlap with "Migration and Climate Change: An Overview, " by Etienne Piquet, Antoine Pécoud, and Paul de Guchteneire in Refugee Survey Quarterly (June 8, 2011), Oxford Journals.